(untitled) - Tolkien, J. R. R. (John Ronald Reuel) (Boston, 2003)
"The story moves on with a tremendous narrative rush to its climax... extraordinarily imaginative work, part saga, part allegory, and wholly exciting." Daily Telegraph
Keywords: Baggins, frodo (fictitious character),Middle earth (imaginary place),Fantasy fiction, english; Fiction,Fiction